Day care days - Barrett, Mary Brigid; Murphy, Patti Beling (Boston, Mass. : Little, Brown, 1999)
A little boy recounts the events of his family$1 (Bs busy day, from waking up, getting dressed and off to day care, until his Daddy picks him and his baby brother up and brings them home.s
Keywords: Family life -- Fiction; Day care centers -- Fiction; Stories in rhyme